Review: Michael Bollig, Shaping the African Savannah: From Capitalist Frontier to Arid Eden in Namibia, Cambridge, Cambridge University Press, 2020 (Journal of Namibian Studies : History Politics Culture, 2021)
Review of: Michael Bollig, Shaping the African Savannah: From Capitalist Frontier to Arid Eden in Namibia, Cambridge, Cambridge University Press, 2020.